2015
DOI: 10.1111/jbi.12571
|View full text |Cite
|
Sign up to set email alerts
|

Where did all the trees come from? A novel multispecies approach reveals the impacts of biogeographical history and functional diversity on rain forest assembly

Abstract: Aim We take advantage of next generation sequencing-based technology to assess how landscape-level dynamics, biogeographical history and functional factors shape the distribution of genetic diversity in rain forest trees. To achieve this, we explore chloroplast genomic diversity and divergence patterns across multiple, co-distributed species from three major centres of rain forest diversity.Location Subtropical rain forests in south-eastern Australia: Nightcap-Border Ranges, Dorrigo and Washpool.Methods We ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 45 publications
3
62
0
Order By: Relevance
“…In our study, we show that important refugial areas in AWT and NNSW (Nightcap‐Border Ranges and Dorrigo) may have resisted Sunda invasion. We observed the expected lower proportions of Sunda lineages in NNSW including the Nightcap‐Border Ranges and Dorrigo regions (compared to AWT), and note a similar pattern in Washpool, a primarily recolonized area (Kooyman et al., ; Rossetto, McPherson, et al., ). This suggests that while Sahul lineages were able to recolonize Washpool from neighbouring refugia (within Nightcap‐Border Ranges and Dorrigo), the number of Sunda lineages able to colonize from source populations (assumed to be further north) was limited.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In our study, we show that important refugial areas in AWT and NNSW (Nightcap‐Border Ranges and Dorrigo) may have resisted Sunda invasion. We observed the expected lower proportions of Sunda lineages in NNSW including the Nightcap‐Border Ranges and Dorrigo regions (compared to AWT), and note a similar pattern in Washpool, a primarily recolonized area (Kooyman et al., ; Rossetto, McPherson, et al., ). This suggests that while Sahul lineages were able to recolonize Washpool from neighbouring refugia (within Nightcap‐Border Ranges and Dorrigo), the number of Sunda lineages able to colonize from source populations (assumed to be further north) was limited.…”
Section: Discussionsupporting
confidence: 69%
“…A significant per‐plot reduction of Sunda species proportion and richness ( p < .001 using Tukey HSD post hoc test, Figure ; Table ) was also observed between Nightcap‐Border Ranges (north) and Dorrigo (to the south). These two areas are separated by the Clarence River Corridor, a previously recognized biogeographical barrier (Rossetto, McPherson, et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of those habitat contractions was the retreat of rain forest to refugia in the wettest places. Depending on the topography and proximity to the coast, the rain forest refugia varied in size and distribution through time, with both the distance between remnant patches and the effective population sizes of local species changing with them (Kooyman et al, ; Mellick et al, ; Rossetto, McPherson, et al, ). For plants, these processes impacted on the fitness and viability of populations, the between‐refugia dynamics and the potential for expansion and recolonization (Rossetto, Crayn, Ford, Ridgeway, & Rymer, ; Rossetto et al, ; ).…”
Section: Discussionmentioning
confidence: 99%
“…This is not an unusual finding (but see [64]). For example, in a whole chloroplast genome study of 71 rainforest taxa, Rossetto et al [65] found 75% of the trees sequenced (up to 18 individuals per species) had less than 25 single nucleotide polymorphisms across an average of 122,373 bp sequenced. Diazgranados & Barber [66], working with 110 species in the subtribe Espeletiinae Cuatrec., Asteraceae, found that most chloroplast regions screened were uninformative or the variability was too low to resolve phylogenetic relationships.…”
Section: Molecular Markersmentioning
confidence: 99%